Comparison of Metformin and Insulin Monotherapy with Combined Metformin and Insulin Therapy in Patients of Type 2 Diabetes with HbA1c > 7%. - Galani, Varsha (International Journal of Pharmaceutical & Biological Archive, 2011)
Early and intensive glycemic control is necessary to prevent or minimize the development of micro vascular and macro vascular complications in individuals with type 2 diabetes mellitus. In the present study, clinical efficacy of the metformin, insulin and metformin plus insulin was compared in the patients of type 2 diabetes mellitus with HbA1c > 7%. In an open-label, monocentric controlled trial, 45 patients of type 2 diabetes with HbA1c > 7% were randomly divided in to three groups (n=15). First group treated with metformin (1000 mg), second group treated with insulin (10 IU) and third group treated with insulin (10 IU) plus metformin (500 mg) for 3 months duration. Fasting blood glucose, postprandial blood glucose and HbA1c level were measured before treatment and after 3 months of each treatment course. Result of this study indicated that significant reduction in fasting and postprandial blood glucose level was observed in all treatment groups. Significant reduction in HbA1c level was also observed in all treated patients. Combined treatment of metformin and insulin caused 26% more reduction in HbA1c level than metformin and 11.41% more reduction than insulin monotherapy. In conclusion, therapy with insulin alone or with metformin in patients having poor glycemic control may be a useful and safe therapeutic approach in type 2 diabetes.